APPLICATION OF TRAUMEEL S IN THE TREATMENT OF INFLAMMATORY DISEASES OF THE MAXILLOFACIAL REGION - Shokhrukh Shavkat Ugli Mustafokulov, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract   This review article discusses current approaches to the use of Traumeel S in the management  of  inflammatory  diseases  of  the  maxillofacial  region,  including periodontitis,  peri-implantitis,  abscesses,  and  phlegmons.  The  mechanisms  of inflammation and the influence of homeopathic remedies, particularly Traumeel S, on these processes are analyzed. Special attention is paid to the effectiveness of the drug in  the  postoperative  period  for  reducing  edema  and  pain  syndrome,  as  well  as optimizing wound healing. The efficacy of combined treatment using Traumeel S in conjunction with other medications is also considered. In addition, the article presents the results of clinical studies confirming the high effectiveness of this homeopathic preparation in patients with hypersensitivity to conventional pharmaceutical agents.